(untitled) - Mizrahi, Abe (New York, 1993)
This book is divided into three independent parts: Linear algebra, Probability, and Discrete mathematics.
Keywords: Toán kinh tế,Business mathematics,Social science,Khoa học xã hội; Mathematics,Toán học